Numerical study on the balance of energy of a floating oscillating water column wave energy converter and breakwater hybrid system - Ram, Giri; Saad, Mohd Rashdan; Md Naiem, Mohd Azzeri; Zainal Abidin, Noh; Imai, Yasutaka; Ramli, Muhammad Zahir; Abdul Rahman, Mohd Rosdzimin (Elsevier Ltd., 2025)
The conversion of ocean wave energy into useful electrical energy has garnered attention in recent years, mainly due to the global initiative to transition towards clean and renewable energy. Among the various types of wave energy converters, the bottom-detached oscillating water column (OWC) is of particular interest, due to its ability to be installed in the vast near-shore and offshore regions of the ocean. Several studies have looked into the bottom-detached OWC. A fraction of these studies focus on the inclusion of an independent breakwater to improve the performance of the OWC. The aim of this study is to numerically investigate the hydrodynamic performance of a bottom-detached OWC and breakwater hybrid system using an energy balance approach, that is based on the conservation of energy principle. Hydrodynamic coefficients, vorticity magnitudes and a formulated and proposed energy balance equation were calculated and results were analysed. Numerical simulation was conducted using computational fluid dynamics solver ANSYS Fluent, whereby the numerical model was divided into two OWC motion types, four cases of gap lengths and six cases of incident wave frequency. Results show that the proposed energy balance equation accurately interprets the results of OWC-breakwater hybrid system. Fixed OWC shows a significantly higher efficiency than floating OWC case, as do wider gaps 0.07 m and 0.09 m and frequency 5 rad/s. Cases with high extraction energy percentage also show high energy loss. Major sources of energy loss are identified to be heave movement of OWC and vortex formation in OWC.